Efeito comparativo da fotobiomodulação local e vascular sistêmica durante o processo de hipertrofia compensatória do músculo plantar em ratos - Araujo, Andréia Martinelli de Siqueira (2022)
Compensatory hypertrophy (CH) is an adaptation that occurs in the muscle in response to overload, resulting in an increase in muscle fiber size. Photobiomodulation (PBM) has demonstrated positive effects on skeletal muscle during the HC process including modulation of inflammatory cytokines, collagen reduction and increase in cross-sectional area (CSA). The aim of this study was to compare the effects of systemic transcutaneous vascular photobiomodulation (VPBM) and infrared local PBM (LPBM) on morphological and functional changes in muscle tissue during the HC process in rats. Thirty-five Wistar rats were used, divided into 4 groups: Control (n=5); Hypertrophy (H) (n=10), Hypertrophy + vascular photobiomodulation (H + PBMV) (n=10) and Hypertrophy + local photobiomodulation (H + LPBM) (10). Hypertrophy was induced by the ablation model of the synergistic muscles of the plantar. Local PBM was performed with a low-intensity laser (AsGaAl, λ 780 nm; 40 mW; radiant exposure 10 J/cm2; 10 seconds at each point; 8 points over the plantar region; 3.2 J) and vascular PBM at the parameters of 80 J/cm2 .40mW, for 80 seconds in a single point, 3.2 J, applied over the caudal vein. The animals were evaluated after 7 and 14 days of PBM application for gait functional capacity and mechanical sensitivity using the sciatic functional index (SFI) test and the von Frey test, respectively. After these evaluations, the animals were euthanized and the plantar muscles were removed and used for analyzes that included the determination of the weight ratio of the left and right muscles (L/R) and analysis of morphological aspects by histology technique with staining H&E for determination of CSA and muscle fiber diameter. Histological analysis showed an increase in CSA in the H+PBMV group compared to the H group after 7 and 14 days and an increase in CSA in the H+VPBM group when compared to the H+LPBM group after 14 days. After 7 days there was an increase in muscle fiber diameter in the H+PBMV group when compared to the H group, and at 14 days an increase in fiber diameter was found in both groups that received PBM (H+LPBM and H +VPBM) when compared to the non-irradiated group (H), this increase being more pronounced in the PBMV group compared to the PBML group. The mass ratio (R/L) in groups H, H+LPBM and H+VPBM reduced when compared to the control group after 7 days. At 14 days, there was a reduction in this relationship in groups H and H+LPBM compared to the control group and maintenance in the H+VPBM group showing mass values that did not differ from the values of the control group. Regarding mechanical sensitivity, both H and irradiated groups showed a reduction in sensitivity compared to the control group after 7 and 14 days and there was no difference between groups H, H+VPBM and H+LPBM in any of the experimental periods. In the functional analysis of gait (SFI), all groups showed lower functionality when compared to the control group after 7 days. In 14 days, both irradiated groups reestablished the normal functionality index, close to the control group. Group H remained with higher scores when compared to the control group. In conclusion, both forms of irradiation positively modulate the recovery process and the morphological aspects of functionality during a HC. The comparison of both irradiations showed more pronounced effects of VPBM with regard to the increase in CSA, fiber diameter and maintenance of mass volume and similar results for both forms, local and vascular, with regard to aspects of sensitivity mechanics and the reestablishment of the normal index of gait functionality.